Experimental validation of finite elements model in hip fracture and its clinical applicability - Larrainzar-Garijo, R.; Caeiro, J.R.; Marco, M.; Giner, E.; Miguélez, M.H. (Revista española de cirugía ortopédica y traumatología, 2019)
Fracture of the proximal extremity of the femur is the subject of research interest. The complexity of the bone framework and the structural inefficiency associated with ageing leave many variables yet to be understood from an experimental perspective. However, there is no clearly defined structural and biomechanical research model for hip fracture. The hypothesis of this paper is that it is possible to create a computational experimentation model that characterises the bone of the proximal extremity of the femur as a heterogeneous material from directly translating the mechanical parameters obtained from anatomical experimentation specimens. An experimental paper comparing real experimentation on cadavers and a numerical model based on finite element analysis (FEA). The variables uses were: the start point of the fracture, propagation of the fracture, progressive load and maximum load until fracture. The real mechanical parameters obtained from the anatomical specimens were translated to the computational model based on the relationship between the Hounsfield units of the high resolution CAT scan and the bone mineral density of each virtual element, whereas the propagation of the fracture was modelled by the research team's own computational design, reducing the mechanical properties of the damaged elements as the fracture line advanced. The computational model was able to determine the start point of the fracture, with a slight tendency towards anatomical medialisation of this point compared to what happened experimentally. The degree of correlation was very high on comparing the real value of progressive deformation of the samples compared to that obtained by the computational model. Over 32 points analysed, a slope of 1.03 in lineal regression was obtained, with a relative error between the deformations of 16% and a Pearson's coefficient of R2=.99. The computational model slightly underestimated the maximum fracture load, with a relative error of approximately 10%. The FEA computational model developed by this multi-disciplinary research team could be considered, as a whole, a complete FEA model of the proximal extremity of the femur with future clinical applicability since it was able to simulate and imitate the biomechanical behaviour of human femurs contrasted with a traditional experimental model made from anatomical specimens. On this basis, qualitative and quantitative interactions can be assessed which consolidate it as a powerful computational experimentation test bench for the human proximal femur. La fractura de la extremidad proximal de fémur es objeto de interés en investigación. La complejidad del entramado óseo y la ineficiencia estructural asociada al envejecimiento hacen que existan muchas variables todavía por comprender desde el punto de vista experimental, pero no existe un modelo de investigación estructural y biomecánico de la fractura de cadera claramente definido. La hipótesis de este trabajo es que es posible desarrollar un modelo de experimentación computacional que caracterice el hueso de la extremidad proximal del fémur como un material heterogéneo a partir de la traslación directa de los parámetros mecánicos obtenidos de piezas anatómicas de experimentación. Trabajo experimental que compara la experimentación real en cadáver y un modelo numérico basado en análisis de elementos finitos (AEF). Las variables que se han empleado son: punto de inicio de la fractura, su propagación, carga progresiva y la carga máxima hasta fractura. Al modelo computacional se trasladaron los parámetros mecánicos reales obtenidos de las piezas anatómicas basándose en la relación entre las unidades Hounsfield de la TAC de alta resolución y la densidad mineral ósea de cada elemento virtual, mientras que la propagación de la fractura se modeló mediante desarrollo computacional propio del equipo investigador, con disminución de las propiedades mecánicas de los elementos dañados conforme avanza la línea fractuaria. El modelo computacional fue capaz de determinar el punto de inicio de la fractura, con una discreta tendencia a la medialización anatómica de dicho punto respecto a lo ocurrido de manera experimental. El grado de correlación fue muy alto al comparar el valor real de deformación progresiva de las muestras frente al obtenido por el modelo computacional. Sobre 32 puntos analizados, se obtuvo una pendiente de 1,03 en regresión lineal, con un error relativo entre las deformaciones del 6% y un coeficiente de Pearson de R2=0,99. El modelo computacional infraestimó discretamente la carga máxima de fractura, con un error relativo aproximado al 10%. El modelo computacional de AEF desarrollado por este equipo investigador multidisciplinar se puede considerar, en conjunto, un modelo completo de AEF de la extremidad proximal del fémur con aplicabilidad clínica futura al ser capaz de simular e imitar el comportamiento biomecánico de fémures humanos contrastado con un modelo experimental clásico realizado en piezas anatómicas. Sobre esta base podrán evaluarse interacciones cualitativas y cuantitativas que lo consoliden como un potente banco de ensayos de experimentación computacional sobre el fémur proximal humano.